From negative to positive integration? European state aid control through soft and hard law - Michael Blauberger (Max Planck Institute for the Study of Societies, 2008)
European state aid control, a part of competition policy, typically follows the logic of negative integration. It significantly constrains the potential for Member States to distort competition by reducing their ability to subsidize industry. In addition, this paper argues, ambiguous Treaty rules and heterogeneous Member States' preferences have enabled the European Commission to act as a supranational entrepreneur, not only enforcing the prohibition of distortive state aid, but also developing its own vision of good state aid policy. In order to prevent or to settle political conflict about individual decisions, the Commission has sought to establish more general criteria for the state aid which it still deems admissible. These criteria have been codified into a complex system of soft law and, more recently, hard state aid law. The Commission has thus created positive integration from above and increasingly influences the objectives of national state aid policies.
Keywords: 300; EU-Beihilfenkontrolle; Europäische Integration; Nationalstaat; EU-Staaten